The impact of capital market development on economic growth among MENA region countries - Jiuma Mo, Intisar (2017)
Middle East and North African (MENA) region is home to nearly 60% of the 1.4 trillion barrels of proven crude oil reserves and 46% of the 192 trillion standard cubic meters of natural gas reserves (OPEC, 2010). Although the capital market plays an important role in economic development in many countries, (MENA) region the role is not so clear. The region has participated less in the globalization and integration of international capital markets than have Asian and Latin American countries. Capital flows into the MENA region have been small. Countries in the region have had almost no direct access to the capital markets of industrial countries. The region has made only limited use of market-based income-hedging devices (such as product insurance and forward markets) despite its vulnerability to international price developments. Accordingly capital markets in the region are assumed to have not effectively utilized to generate economic growth due to structural and cultural factors albeit their potential prospects. Hence this study analyses and measures the historical impact of capital market development on the economic growth of four leading countries in the MENA region; Egypt and Tunisia (as non-oil driven economies); and Saudi Arabia and Kuwait (as oil exporter economies). In order to achieve the research aim, a quantitative method approach is adopted. Using 13 time periods (years) from 2002 to 2014 as the annual time-series data of the four countries, this study focuses on indicators that reflect the state of development of the capital market. This study used four variables as a General Index proxy for capital market development; (1) market capitalization ratio to GDP, (2) value of shares traded, (3) Number of shares traded, and (4) number of transactions, while gross domestic product (GDP) was used as a proxy for economic growth. In addition, the study used six macroeconomic variables as control variables, including (GDP/capita), saving rate ratio to GDP, investment rate ratio to GDP, interest rates, inflation, and exchange rates. The data of this study were analysed using Ordinary Least Squares (OLS) regression to examine the capital market development and economic growth relationship for the four countries. Pooled OLS regression analysis was adopted to examine the effects of development of the capital market on the economic growth of the countries as a group. The results of OLS regression indicate that the Egyptian capital market development had significant effects on economic growth, although there were mixed results when different proxies of capital market development indicators were used. In Tunisia, Saudi Arabia, and Kuwait, the level of capital market development had little influence on economic growth, and most of the results were insignificant when different proxies of capital market development indicators were used. However, using the OLS regression analysis model for the four countries combined showed that the development of the capital market had a significant impact on the economic growth of these countries. This study concluded that economic policy options consistent with maximizing economic performance and aiming at elevating economic growth should be developed through the integration of capital markets of the region. Therefore, policy makers should provide incentives to integrate the capital markets and unify economic structures where possible, by diverting funds to investment to further stimulate the growth of their economies. Keywords; Capital market development, Economic growth, Egypt, Tunisia, Saudi Arabia, Kuwait, MENA region